A NEED ANALYSIS OF INNOVATIVE CULTURE-BASED ENGLISH LEARNING MODEL FOR NON-ENGLISH DEPARTMENT STUDENTS AT BINA NUSANTARA UNIVERSITY - Aryusmar Aryusmar; Muhartoyo Muhartoyo (Universitas Ahmad Dahlan)
In line with Binus University mission the graduates are expected to get involved themselves in the global community by either working for global companies or being self-employed professionals or entrepreneurs with world-wide perspective. This can only be successfully achieved when their graduate competence includes the ability in using English for global professional communication. English is widely used in activities of economy, trade, industry, education and culture. This paper presents a need analysis of non-English Department students at Bina Nusantara University to acquire English language and culture simultaneously. The analysis is based on the experience of teaching English for non-English Department students at Bina Nusantara University and based on the analysis of compiled concepts, theories and references obtained through comprehensive library research. The need analysis concludes that there is an urgent need to develop an Innovative Culture-Based English Learning Model to Enable Non-English Department Students at Bina Nusantara University to Master English Language for Professional Development. New learning culture also needs to be introduced to achieve the learning outcomes set out in the Culture-based Learning model.